Bibliometric Insights into the "Kathmandu School of Law Review" - Neupane, Alaka; Karki, Tej Bahadur; Neupane, Avinash (NPRC Journal of Multidisciplinary Research, 2024)
This bibliometric study analyzes the academic reach, thematic focus, and collaboration trends of the Kathmandu School of Law Review (KSLR). Through keyword analysis, the research highlights recurring themes such as human rights, governance, policy-making, and development, reflecting a multidisciplinary approach to legal scholarship. Visualizations of co-authorship networks reveal limited collaboration among scholars, suggesting opportunities for the journal to foster joint publications and interdisciplinary partnerships. Citation network analysis indicates a niche area of research with a few central authors like Puja Mitra and Yubaraj Sangroula, while the low overall citation count points to the need for broader academic engagement and visibility. Bibliographic coupling maps show emerging research clusters, indicating the potential for KSLR to build authority in key areas such as South Asian legal systems and international human rights. The study concludes with recommendations for KSLR to increase global outreach, promote interdisciplinary studies, and enhance academic collaboration to strengthen its impact within and beyond the region.